Operationalizing vulnerability for social–ecological integration in conservation and natural resource management. Issue 1 (1st October 2019) - Thiault, Lauric; Gelcich, Stefan; Marshall, Nadine; Marshall, Paul; Chlous, Frédérique; Claudet, Joachim
Abstract: Sustaining human well‐being is intimately linked to maintaining productive and healthy ecosystems. Avoiding trade‐offs and fostering co‐benefits is however challenging. Here, we present an operational approach that integrates biodiversity conservation, human development, and natural resource management by (1) examining resource and resource user interactions through the lens of social–ecological vulnerability (i.e., encompassing exposure, sensitivity, and adaptive capacity); (2) identifying "ecocentric" and "sociocentric" interventions that directly address the ecological or social sources of vulnerability; (3) prioritizing those expected to yield co‐benefits and minimize trade‐offs; and (4) selecting interventions that are best suited to the broader local context. Application of this approach to a coral reef fishery in French Polynesia recommended a portfolio of development‐, livelihood‐, and ecosystem‐based interventions, thus suggesting a shift from the current resource‐focused approach toward a more social–ecological perspective. Our vulnerability‐based approach provides practitioners with a valuable tool for broadening their set of management options, leading to escape from panacea traps.